Fuel cells as distributed generation - Cruden, A.; Houghton, Tom; Gair, S.; Duerr, M.; Agnew, G.; Stewart, E.; Lutz, A. (Sage Publications for Institution of Mechanical Engineers, 2008)
This paper presents an overview of fuel cells as a form of distributed generation within the context of a highly distributed power system, by discussing some example demonstration systems categorized by the type of primary fuel used, namely fossil fuels, hydrogen gas, or biofuels. It discusses the background to fuel cells as a stationary, grid connected, power source, briefly compared with conventional thermal electrical generation, while describing the main characteristics of their performance and an electric equivalent circuit model. Additionally, it presents a view of the current state of commercialization of fuel cell technology for stationary power applications.